Community structure and estimation of aboveground biomass and carbon stock of beach forest in San Joaquin, Iloilo, Philippines - Londres, Ross Martin B.
A forest provides a habitat to many living creatures and a source of goods and services for daily human needs. One form of forest is the beach forest, a narrow strip composed of creepers, shrubs, littoral trees that have adapted to the harsh environmental conditions located above the high tide level. Beach forest can provide protection against the adverse effects of typhoons in coastal communities and can mitigate global climate change due to the ability of plants to sequester and store carbon dioxide from the atmosphere. However many of our beach forests have been converted to many uses, while the remaining face the threat of complete deforestation arising from human activities. Unfortunately, there is little or scanty information about these forests in the Philippines and elsewhere. Thus, the need for this study. This study aimed to assess the community structure and estimate the carbon stock and aboveground biomass of beach forest in San Joaquin, Iloilo, Philippines. Specifically, it aimed to: a) Identify the beach forest species present in the area; b) Describe the community structure in terms of: species composition, diameter at breast height and stand height, stand basal area, importance value, index of biodiversity, species richness and evenness; c) Determine aboveground biomass and carbon stock; and d) Determine whether there is a relationship between beach forest species mean DBH and carbon stock and between mean height and carbon stock. A field survey was conducted using three 100 m transect line with 3 plots each in January 30-31, 2016 in Barangay Lawigan and Sinogbuhan. Results showed a total of 57 beach forest species, belonging to 29 families, with Barangay Lawigan having 44 while Barangay Sinogbuhan with 37 and this includes the relatively un-common Gyrocarpus americanus. Among the species recorded, Pterospermm diversifolium was the relatively dominant species: Sterculia ceramic was the relatively frequent species and Capparis micracantha was the relatively dense species. However, the areas had low diversity (H? = 1.039) that could be attributed to the conversion to residential and recreational areas. Baringtonia asiatica, Sterculia foetida and Gyrocarpus americanus have the highest carbon stock due to their large aboveground biomass. This study provides baseline information useful in the establishment of sustainable efficient conservation strategies for restoration, rehabilitation, and protection of the remaining beach forest in San Joaquin, Iloilo.